2022
DOI: 10.1002/smll.202200673
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Nanocarriers as Theranostics—Advancement from Peptides to Nanocarriers

Abstract: Endogenous targeted radiotherapy is emerging as an integral modality to treat a variety of cancer entities. Nevertheless, despite the positive clinical outcome of the treatment using radiolabeled peptides, small molecules, antibodies, and nanobodies, a high degree of hepatotoxicity and nephrotoxicity still persist. This limits the amount of dose that can be injected. In an attempt to mitigate these side effects, the use of nanocarriers such as nanoparticles (NPs), dendrimers, micelles, liposomes, and nanogels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 130 publications
0
13
0
Order By: Relevance
“…New biomaterials, such as nanoparticles, dendrimers, micelles, liposomes, and nanogels, including nanomedicine, , which could offer more precise pharmacotherapy options with improved safety profiles, especially in cisplatin and antibiotics, could attenuate nephrotoxicity ( Cooper et al, 2014 ; Desai et al, 2022 ). Reports showed that cisplatin conjugated to a polyphosphazene, lipid-coated cisplatin nanoparticle, and cholesterol-tethered platinum II-based nanoparticle could increase the antitumor effect and reduce nephrotoxicity ( Sengupta et al, 2012 ; Guo et al, 2013 ; Patil et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…New biomaterials, such as nanoparticles, dendrimers, micelles, liposomes, and nanogels, including nanomedicine, , which could offer more precise pharmacotherapy options with improved safety profiles, especially in cisplatin and antibiotics, could attenuate nephrotoxicity ( Cooper et al, 2014 ; Desai et al, 2022 ). Reports showed that cisplatin conjugated to a polyphosphazene, lipid-coated cisplatin nanoparticle, and cholesterol-tethered platinum II-based nanoparticle could increase the antitumor effect and reduce nephrotoxicity ( Sengupta et al, 2012 ; Guo et al, 2013 ; Patil et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiopharmaceuticals are one of the most important tools for fighting cancer, and the development of peptide receptor radionuclide therapy (PRRT) depends on the knowledge gathered from radiotherapy [ 90 ]. The mechanistic pathways of radiopharmaceuticals show that some important parameters need to be addressed, such as the complete measurement of physiological and biological functions at the targeted sites ( Figure 2 ) [ 48 ]. PRRT solely depends on the process of amassing radiopharmaceuticals at the definite site, which is regulated by several biological processes such as the transference of biochemical species and enzymatic exchanges.…”
Section: Radiopharmaceuticals With Radiolabelled Peptides Towards Can...mentioning
confidence: 99%
“…β-emitters cause repairable damage to single-strand DNA. Reproduced with permission, copyright JOHN WILLEY AND SONS [ 48 ].…”
Section: Figures Scheme and Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Delivering therapeutic radionuclides into tumors is a promising strategy to enhance the effect of radiation on tumors and decrease radio-toxicity to neighboring normal tissues [ 33 ]. Generally, therapeutic radionuclides (such as 131 I and 90 Y [ 47 ]) are specifically delivered into tumors via suitable tumor-homing carriers, chiefly liposomes, microparticles, nanoparticles, micelles, dendrimers, and hydrogels [ 33 , 48 ]. Here, we describe the utilization of microparticles and nanoparticles in delivering therapeutic radionuclides.…”
Section: Chromatographic Matrices and Corresponding Applications In R...mentioning
confidence: 99%